Implementasi Manajemen Perpustakaan di MI Nurul Islam Jombang - Nurwarniatun (Journal of Islamic Education Management, 2022)
This study focuses on the implementation of general management functions in managing libraries in school and how to increase students interest in reading which in closely related to the library management strategy undertaken. In essence, library management is carried out so that students are able to use school facilities to the maximum and help train students to become a generation that cares about literacy. It cannot be denied that education must balance with this increasingly advanced technology, so that to make students able to compete academically through reading media. That is why library management is very important for the sake of achieve the quality of students in both academic and non-academic fields and prepare a generation capable of responding to the challenges of the times.